2015
DOI: 10.1108/bfj-05-2013-0112
|View full text |Cite
|
Sign up to set email alerts
|

Changing consumer intake of potato, a focus group study

Abstract: Purpose – While potato consumption in Europe and North America declines, other carbohydrate sources increase. The purpose of this paper is to explore factors affecting consumers’ changing consumption behaviour as regards fresh potato. Design/methodology/approach – Six semi-structured focus group interviews were conducted. Thematic analysis was made by means of a theory-driven approach. Findings – Seven categories of factors affecting consumer choice of fresh potato were found and discussed: first, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…In Finland though, the consumption has been relatively stable since the mid-1980s, and in Sweden, there is the tendency to stabilization in the last two decades (Swedish Board of Agriculture 2016; Statbank, Statistics Norway 2016;Statistics Finland 2016). A recent study on consumers' attitudes to potato consumption indicated that different aspects of comfort in relation to the shopping and preparation of potato, rather than health aspects, has had an influence on the declining trend of potato consumption in Sweden (Fernqvist et al 2015), explaining the decrease in consumption of fresh potato in favour of consumption of processed potato, pasta and rice. Nevertheless, potato is still the only major source of carbohydrates for direct human consumption cultivated in the region, as well as an important source of vitamin C and antioxidants, and continues to be a large and important part of peoples' daily diet.…”
Section: Potato Consumption In Sweden Norway and Finlandmentioning
confidence: 99%
“…In Finland though, the consumption has been relatively stable since the mid-1980s, and in Sweden, there is the tendency to stabilization in the last two decades (Swedish Board of Agriculture 2016; Statbank, Statistics Norway 2016;Statistics Finland 2016). A recent study on consumers' attitudes to potato consumption indicated that different aspects of comfort in relation to the shopping and preparation of potato, rather than health aspects, has had an influence on the declining trend of potato consumption in Sweden (Fernqvist et al 2015), explaining the decrease in consumption of fresh potato in favour of consumption of processed potato, pasta and rice. Nevertheless, potato is still the only major source of carbohydrates for direct human consumption cultivated in the region, as well as an important source of vitamin C and antioxidants, and continues to be a large and important part of peoples' daily diet.…”
Section: Potato Consumption In Sweden Norway and Finlandmentioning
confidence: 99%
“…The data from study 2 were analyzed using a one‐way analysis of variance (ANOVA) for the weighted averages based on factor scores to evaluate effects of country of origin, cultivation area, cultivation process, and flavor profile of oysters on consumers' willingness to buy and willingness to pay for the tested oyster labels. Reasons mentioned by consumers explaining their willingness to buy were categorized into themes (country of origin, cultivation area, type of cultivation process, and flavor profile) . Reasons were considered positive when willingness to buy was scored above four, on a seven‐point scale.…”
Section: Methodsmentioning
confidence: 99%
“…Reasons mentioned by consumers explaining their willingness to buy were categorized into themes (country of origin, cultivation area, type of cultivation process, and flavor profile). 19 Reasons were considered positive when willingness to buy was scored above four, on a seven-point scale. Likewise, reasons were considered negative when willingness to buy was scored below four.…”
Section: Statistical Data Analysismentioning
confidence: 99%
“…Agencias gubernamentales, organizaciones sin fines de lucro, investigadores, académicos y expertos en relaciones públicas han descubierto el valor de esta metodología (Morgan, 1998). Para fines de este estudio se seleccionó esta técnica ya que se consideró la apropiada para lograr los objetivos pero también porque ha sido utilizada en el análisis de la problemática del sector primario y en una amplia gama de estudios sociales y de mercadotecnia como lo señalan Fernqvist et al (2015).…”
Section: Figura 1 El Diamante De Porterunclassified